2006
DOI: 10.1163/156916306777835277
|View full text |Cite
|
Sign up to set email alerts
|

Racialized Choices: Chinese Adoption and the `White Noise' of Blackness

Abstract: The transnational, transracial adoption of children provides the opportunity to explore how race binds and differentiates kinship and national belonging, especially when considered in relation to options for adopting both at home and abroad. More specifically, the reasons white parents give for choosing to adopt from China reveal how the normative white, American family is constructed through discourses of foreign and domestic, Asian and black. I explore three themes that contribute to the relative desirabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…Black children, Dorothy Roberts (2002, p. 159) argues, are the "least likely to be adopted." Interviewbased research has shown that many international adoptive parents prefer oversees adoptions precisely because young, healthy, non-African American children are available (Dorow, 2006b;Jacobson, 2008;Kim, 2008).…”
Section: Adoption Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Black children, Dorothy Roberts (2002, p. 159) argues, are the "least likely to be adopted." Interviewbased research has shown that many international adoptive parents prefer oversees adoptions precisely because young, healthy, non-African American children are available (Dorow, 2006b;Jacobson, 2008;Kim, 2008).…”
Section: Adoption Decision Makingmentioning
confidence: 99%
“…Other factors contribute to the decision to pursue an overseas placement instead of a domestic one; in particular, race and age (Dorow, 2006b;Jacobson 2008;Kim, 2008). The desire for a non-African American infant strongly shaped many participants' decisions to adopt from oversees.…”
Section: "Dangerous" Domestic Placementsmentioning
confidence: 99%
“…In her recent study, for example, Dorow (2006a) analyzes how China‐U.S adoption ‘unsettles’ and ‘reproduces’ racial hierarchy. She argues for the importance of ‘the American imaginary of China and its relationship to the black‐white binary’ when considering race in the adoption of Chinese children into white families (Dorow 2006a: 358). More specifically, black children have become ‘the constitutive outside’ to foreign Asian children (Dorow 2006a: 360).…”
Section: Triangulating Race: Reifying Racial Hierarchymentioning
confidence: 99%
“…Empirical research suggests that White adoptive parents often take a colour-blind approach to transracial adoption, believing that race will not be an issue for their children (Taylor & Thornton, 1996). This colour-blind -if wellmeaning -approach to racial/ethnic minority children may allow some parents to overlook potential challenges their children will face (Dorow, 2006).…”
Section: The Transracial Adoption Debatementioning
confidence: 99%